2008
DOI: 10.1002/cncr.23669
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 dose‐escalation study of a GM‐CSF‐secreting, allogeneic, cellular immunotherapy for metastatic hormone‐refractory prostate cancer

Abstract: BACKGROUNDThis open‐label, multicenter, dose‐escalation study evaluated multiple dose levels of immunotherapy in patients with metastatic hormone‐refractory prostate cancer (HRPC). The immunotherapy, based on the GVAX platform, consisted of 2 allogeneic prostate‐carcinoma cell lines modified to secrete granulocyte‐macrophage‐colony‐stimulating factor (GM‐CSF).METHODSDose levels ranged from 100 × 106 cells q28d × 6 to 500 × 106 cells prime/300 × 106 cells boost q14d × 11. Endpoints included safety, immunogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 48 publications
1
109
0
2
Order By: Relevance
“…In phase I/II trials, chemotherapy-naïve patients with "hormone-refractory" prostate cancer, received GVAX as a priming intradermal injection followed by boost injections every 2 weeks (five different dose levels). The results of these trials showed that GVAX was well tolerated with a safe toxicity profile, as well as effectiveness, demonstrating a median OS of 35 months in the high-dose group of patients (19). Following these results, two phase III trials were designed to evaluate GVAX in mCRPC patients.…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…In phase I/II trials, chemotherapy-naïve patients with "hormone-refractory" prostate cancer, received GVAX as a priming intradermal injection followed by boost injections every 2 weeks (five different dose levels). The results of these trials showed that GVAX was well tolerated with a safe toxicity profile, as well as effectiveness, demonstrating a median OS of 35 months in the high-dose group of patients (19). Following these results, two phase III trials were designed to evaluate GVAX in mCRPC patients.…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…In the other hand, the use of allogeneic tumour cell lines for the whole-tumourcell vaccination was favored because of its ability to introduce multiple antigens and therefore to stimulate a better immune response. An example to this class of cancer vaccines is called GVAX which uses Allogeneic Prostate Cancer Cell Lines VITAL-1 and VITAL-2 that are manipulated to secrete GM-CSF (Higano et al, 2008). Despite its success in phase I and II clinical trials, the application of GVAX was terminated in phase III clinical trials against prostate cancer due to the increased rate of deaths and the low chance of reaching to its end point (Drake, 2009).…”
Section: Autologous or Allogeneic Whole-tumour-cell Vaccinesmentioning
confidence: 99%
“…The trial demonstrated that patients receiving the vaccine had a median OS of 26.2 mo, comparable to patients that receive chemotherapy. 77 Based on the findings of these small phase I/II trials, two large Phase III randomized studies (VITAL-1 and VITAL-2) were developed to test the clinical efficacy of GVAX in treating metastatic prostate cancer. 78 Production of GVAX was halted after both VITAL-1 and VITAL-2 were terminated due to the inefficacy of GVAX and excessive deaths, respectively.…”
Section: Prostate Cancermentioning
confidence: 99%